1988
DOI: 10.1073/pnas.85.9.3155
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical relationship between atriopeptin plasma levels and diuresis-natriuresis induced by acute volume expansion.

Abstract: Surgical removal of one or both atrial appendages was employed in rats to reduce the intrinsic stores of atriopeptin (AP). In conscious rats (with intact baroreceptor reflexes), bilateral or unilateral atrial appendectomy suppressed the diuresis and natriuresis produced by acute volume expansion. Surprisingly, volume expansion (with 4% bovine serum albumin in saline at 1.5 ml/kg per min for 15 min) did not result in an increase in plasma AP immunoreactivity (APir) in control or atrial-appendectomized conscious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
1
11
0
2
Order By: Relevance
“…If this is the case, then ATX may have attenuated the release of this factor. This hypothesis is supported by other investigations (10,27,28). Cowley et al (27,28) found that ANF did not increase after acute saline expansion and that bilateral atrial resection attenuated the increase in sodium excretion.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…If this is the case, then ATX may have attenuated the release of this factor. This hypothesis is supported by other investigations (10,27,28). Cowley et al (27,28) found that ANF did not increase after acute saline expansion and that bilateral atrial resection attenuated the increase in sodium excretion.…”
Section: Discussionsupporting
confidence: 52%
“…They concluded that an unidentified factor, with diuretic and natriuretic capabilities, is released after volume expansion, and that the release of this factor is removed by atrial resection. Sakata et al (10) carried out a similar experiment in conscious rats and demonstrated that ATX attenuated volume expansion-induced increases in sodium excretion. Volume expansion also did not increase ANF in these animals.…”
Section: Discussionmentioning
confidence: 93%
“…The present results suggest the involvement of LPBN serotonergic mechanisms in the regulation of urinary sodium, potassium and water excretion, and hormonal responses to acute isotonic blood volume expansion. serotonin; natriuresis; atrial natriuretic peptide; oxytocin; vasopressin ISOTONIC BLOOD VOLUME expansion, by reflex mechanisms, induces a series of regulatory responses, including the inhibition of the sympathetic outflow to the kidney, heart, and blood vessels, reduction of renin and vasopressin (VP) secretion, and increase in the levels of circulating atrial natriuretic peptide (ANP) and oxytocin (OT) that leads to diuresis and natriuresis (1,2,12,14,20,24,45,53).There are several reports demonstrating the correlation between natriuresis and diuresis and plasma ANP levels in response to systemic volume expansion, e.g., atrial balloon inflation, blood volume expansion, salt load, and water immersion (4,7,17,32,50,59). These responses depend on the activation of sinoaortic baroreceptors and/or cardiopulmonary receptor afferents located in the atria, lungs, great veins, and ventricles that project to the nucleus of the solitary tract (NTS) (1, 12, 22).…”
mentioning
confidence: 99%
“…There are several reports demonstrating the correlation between natriuresis and diuresis and plasma ANP levels in response to systemic volume expansion, e.g., atrial balloon inflation, blood volume expansion, salt load, and water immersion (4,7,17,32,50,59). These responses depend on the activation of sinoaortic baroreceptors and/or cardiopulmonary receptor afferents located in the atria, lungs, great veins, and ventricles that project to the nucleus of the solitary tract (NTS) (1, 12, 22).…”
mentioning
confidence: 99%
“…Although the role of ANP in the natriuresis ofisoncotic ECFV expansion in the conscious rat is still controversial [41], most data are in favor of its role in the natriuresis following ECFV expansion [for ref., see 15], Whatever its role in fluid expansion may be, our present data also exclude DA as mediator of ANP secretion or of a renal action of ANP via DA-2 receptors during acute ECFV expansion.…”
Section: Discussionmentioning
confidence: 99%